Potential and Prospects of Fodder Legumes in rice fallows - Meera Menon V (Department of Agronomy, College of Horticulture, 1987)
An experiment was conducted in the Agricultural Research Station , Mannuthy during third crop season of 1985-’86 and first crop season of 1986-’87 to evaluate the relative performance of fodder legumes in rice fallows and their residual effect on the succeeding crop of rice under graded levels of N. The experiment, replicated thrice, was laid out in a split plot design with seven treatments – six fodder legumes (sannhemp, soya bean, rice bean, velvet bean, cowpea and black gram and a fallow- as main plot treatments and two N levels (52.5 and 70 kg/ha) applied to kharif rice as sub-plot treatments. The results revealed that sannhemp gave a fodder yield of 21 t/ha in rice fallows which was significantly superior to all other treatments. An increase in soil organic carbon, total and available N was also noticed. Soil organic carbon and total N was highest in the cowpea cropped plot. Available N in the soil was highest in the velvet bean cropped plot and the fallow plot recorded the lowest values. Increased rice grain yield was recorded after legumes compared to fallow and the highest grain yield was recorded after velvet bean followed by that after sannhemp cowpea and black gram. Application of N at the recommended dose of 70 kg/ha produced superior yields compared to N at 52.5 kg/ha. Rice crop succeeding fodder legumes with 75% N produced grain yield comparable to that after fallow receiving 100% N. The net income and returns per rupee invested were highest after the sannhemp-rice sequence followed by the cowpea-rice sequence. The results proved that 25% N could be saved in the case of rice after legumes. The study also showed the superiority of sannhemp and cowpea in fodder yield and residual effect in the succeeding rice crop.